Experiences of Socialism in Romanian Exhibitions: Ethical Implications of Display, Invisibility, and Engagement - Maria Cristache (National Museum of the Romanian Peasant, 2021)
The representation of tangible and intangible heritage from the socialist period in Romania has increased and diversified since the House of the People opened for visitors in 1994. Permanent and temporary exhibitions focused on various aspects of life under socialism—from food, housing, and entertainment to the lifestyle of the Ceaușescu couple—have flourished especially in the 2010s. In this article, I examine the different ways in which exhibitions represent the socialist past by displaying objects linked to consumption, leisure, and domesticity and by organizing interactive experiences around the material culture and spaces associated with socialism. The main questions addressed are: Whose perspectives and experiences of the socialist period do these exhibitions represent? What are the direct and indirect ways in which these exhibitions make political commentaries? What are the ethical issues raised by the strong interactive component of some of these experiences?